Highly selective transformation of poly[(R)-3-hydroxybutyric acid] into trans-crotonic acid by catalytic thermal degradation. - Ariffin, Hidayah; Nishida, Haruo; Shirai, Yoshihito; Hassan, Mohd Ali (Elsevier, 2010)
Highly selective transformation of poly[(R)-3-hydroxybutyric acid] (PHB) into trans-crotonic acid was achieved by thermal degradation using Mg compounds: MgO and Mg(OH)2 as catalysts. Through catalytic action, not only the temperature and Ea value of degradation were lowered by 40–50 °C and 11–14 kJ mol−1, respectively, but also significant changes in the selectivity of pyrolyzates were observed. Notably, Mg(OH)2 showed nearly complete selectivity (∼100%) to trans-crotonic acid. Kinetic analysis of TG profiles revealed that the catalytic thermal degradation of PHB was initiated by some random degradation reactions, followed by the unzipping β-elimination from crotonate chain-ends as a main process. It was suggested that the Mg catalysts promote the totality of the β-elimination reactions by acting throughout the beginning and main processes, resulting in a lowering in the degradation temperature and the completely selective transformation of PHB.